Averages associated to the energy momentum tensor and study of a two scale system in general relativity - Boero, Ezequiel Fernando (2014)
Ponencia presentada en la 2nd Argentinian-Brazilian Meeting on Gravitation, Relativistic Astrophysics and Cosmology (GRACo II). Buenos Aires, Argentina, April 22-25, 2014.